Low 3,6-dichloro-o-anisic acid concentration application inhibits calyx senescence and maintains Valencia Late oranges' postharvest quality during ambient storage in Ghana - Nasiru Alhassan (Journal of Horticulture and Postharvest Research)
Purpose: This study determined whether postharvest application with low 3,6-dichloro-o-anisic acid concentration could inhibit calyx senescence and preserve internal and external qualities of Valencia Late oranges during extended storage. Research method: The experiments were conducted using a completely randomized design with three replicates of 50 fruits for each treatment. The oranges fruits were dipped in four treatment concentrations; control (0), 0.01, 0.03, or 0.05 mmol L-1 in experiment 1, and control (0), 0.003, and 0.01 mmol L-1 in experiment 2 for one minute. Post-treatment, the oranges were kept in solid cardboard boxes as individual treatment units (n = 50 fruits) with three units comprising a treatment and held at an ambient temperature (25 ± 2°C) and a 60%–65% RH. Oranges were evaluated every seven days for four weeks. Findings: The results showed that fruit dipped at 0.01 mmol L-1 for both experiments resulted in lower calyx browning and drop, weight loss, and fruit firmness compared to control and higher dicamba concentrations. Moreover, the treatment delayed the increase in total soluble solids and the decrease in titratable acidity, slowing the maturation rate. Research limitation: This study could not evaluate fruit carbon dioxide and ethylene production during storage to understand their impact on other quality changes due to lack of Gas Chromatography machines in the resident laboratory. Originality/Value: The results demonstrate the effects of dicamba treatments in delaying detrimental calyx changes and retaining fruit integrity during storage.